Between Novak and Maritain: The discussion on the capitalist economy in Catholic thought - Hoevel Carlos (Ethics & Bioethics (in Central Europe), 2023)
Although Novak recognizes himself as a disciple of Maritain, especially in his thesis on the Christian origins of democracy, the differences between the two in their views on the capitalist economy are evident. However, in his famous book, The Spirit of Democratic Capitalism, and in other previous works, Novak tries to show some possible bridges between Maritain’s thought and the virtues of American capitalism. This attempt is actually part of a larger project by Novak: that of showing the essential compatibility of Catholicism with capitalism. The purpose of this article is to show, based on Novak’s thought in relation to Maritain, the possibilities and difficulties of this attempt.